2002
DOI: 10.1177/1073858402238511
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Neurotrophins in Neurotransmitter Release

Abstract: The neurotrophins (NTs) have recently been shown to elicit pronounced effects on quantal neurotransmitter release at both central and peripheral nervous system synapses. Due to their activitydependent release, as well as the subcellular localization of both protein and receptor, NTs are ideally suited to modify the strength of neuronal connections by "fine-tuning" synaptic activity through direct actions at presynaptic terminals. Here, using BDNF as a prototypical example, the authors provide an update of rece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
86
0
2

Year Published

2002
2002
2011
2011

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 125 publications
(98 citation statements)
references
References 69 publications
10
86
0
2
Order By: Relevance
“…These larger spines with wider necks are thought to represent spines that acquired AMPA receptors immediately after the induction of long-term potentiation (Matsuzaki et al, 2001;Kasai et al, 2003), and thus enhance spine-dendrite coupling leading to widespread dendritic Ca 2+ signaling during excitatory synaptic transmission (Noguchi et al, 2005). Together with the morphological effects of BDNF on presynaptic terminals (Tyler et al, 2002b) and postsynaptic spine growth and form Pozzo-Miller, 2001, 2003;Alonso et al, 2004), we propose that the larger Ca 2+ signals in spiny dendrites during coincident pre-and postsynaptic activation represent a physiological consequence of the structural BDNF actions at hippocampal synapses. The combination of these structural and physiological effects in the hippocampus may underlie the role of BDNF in the consolidation of synaptic plasticity and hippocampal-dependent learning and memory (Tyler et al, 2002a;Bramham and Messaoudi, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…These larger spines with wider necks are thought to represent spines that acquired AMPA receptors immediately after the induction of long-term potentiation (Matsuzaki et al, 2001;Kasai et al, 2003), and thus enhance spine-dendrite coupling leading to widespread dendritic Ca 2+ signaling during excitatory synaptic transmission (Noguchi et al, 2005). Together with the morphological effects of BDNF on presynaptic terminals (Tyler et al, 2002b) and postsynaptic spine growth and form Pozzo-Miller, 2001, 2003;Alonso et al, 2004), we propose that the larger Ca 2+ signals in spiny dendrites during coincident pre-and postsynaptic activation represent a physiological consequence of the structural BDNF actions at hippocampal synapses. The combination of these structural and physiological effects in the hippocampus may underlie the role of BDNF in the consolidation of synaptic plasticity and hippocampal-dependent learning and memory (Tyler et al, 2002a;Bramham and Messaoudi, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Whereas there is extensive evidence of the modulatory effects of BDNF/TrkB signaling on presynaptic plasticity (for review, see Tyler et al 2002), BDNF has also been shown to have intriguing postsynaptic effects. Changes in postsynaptic responsiveness to presynaptic glutamate release may include enhanced glutamate receptor function, as well as modulation of voltage-gated ion channels.…”
Section: Bdnf and Memory Consolidationmentioning
confidence: 99%
“…Even though BDNF has been repeatedly hypothesized to play a role in learning and memory, evidence of such a role in behaving animals is only beginning to emerge. The extensive literature on the role of NTs in synaptic plasticity, including neurotransmitter release and intracellular signaling cascades, has been reviewed in recent articles (Segal and Greenberg 1996;Schinder and Poo 2000;Thoenen 2000;Poo 2001;Tyler et al 2002). The aims of the present review are to examine the behavioral evidence supporting the involvement of BDNF-triggered intracellular cascades in hippocampal-mediated learning and memory, as well as to evaluate the evidence showing the involvement of those same signaling cascades in forms of hippocampal excitatory synaptic plasticity thought to underlie mechanistically some forms of learning and memory.…”
mentioning
confidence: 99%
“…Upon phosphorylation, ERK is translocated into the nucleus, where it activates the transcription factor cAMP response element-binding protein, thus contributing to the persistent modifications in synaptic efficacy (28)(29)(30)(31). To assess the role of ERK in synaptic potentiation, the pairing procedure was performed in the presence of the ERK inhibitors U0126 and PD98059.…”
Section: Pairing-induced Synaptic Potentiation Requires the Activatiomentioning
confidence: 99%